Wooden pole ladder network model development and verification using finite element analysis. (12th October 2011) - Halevidis, C. D.
SUMMARY In this article, a new resistive ladder network, describing the electrical behavior of the wooden pole, cross arm, and their interconnection, is developed. The network is developed and verified using the results of the finite element analysis of the construction. Good agreement was achieved between the two analyses. In addition, several pole–cross arm topologies were studied, and the effect of the different elements on the total resistance of the construction was quantified. Characteristically, it was found that the use of a steel cross arm instead of a wooden one decreases drastically the total resistance. Also, the use of a steel cross arm brace can reduce the total resistance by up to 37.4%. Copyright © 2011 John Wiley & Sons, Ltd.